Eco-friendly synthesis of ZnO, CuO, and ZnO/CuO nanoparticles using extract of spent Pleurotus ostreatus substrate, and their antioxidant and anticancer activities - Simangele Ngwenya; Nkanyiso J. Sithole; Khosi Ramachela; Doctor M. N. Mthiyane; Mulunda Mwanza; Moganavelli Singh; Damian C. Onwudiwe (Discover Nano)
Abstract Biosynthesis techniques for nanomaterials have advanced significantly, promoting eco-friendly synthesis chemistry as a sustainable alternative to conventional methods. This study presents a novel and environmentally friendly approach for synthesizing nanoparticulate ZnO, CuO, and ZnO/CuO nanocomposites using aqueous extracts of Pleurotus ostreatus spent substrate, is reported. The structural, optical, and morphological properties of the synthesized NPs were analysed. A hexagonal phase of ZnO NPs and a monoclinic phase of CuO NPs were obtained according to the X-ray diffraction analysis. A reduction in the peak intensity of these metal oxides was observed in the ZnO/CuO NPs due to reduced crystallinity. The absorption spectra, obtained from the UV–vis analysis, showed peaks at 354, 365, and 525 nm for the ZnO, CuO, and ZnO/CuO NPs, respectively. An anticancer assay of the NPs was conducted using human embryonic kidney (HEK 293) and cervical carcinoma (HeLa) cell lines, while a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay was used for the antioxidant evaluation. The ZnO, CuO, and ZnO/CuO NPs showed higher antioxidant potency with IC50 of 2.15, 2.16, and 3.18 µg/mL, respectively, than the ascorbic acid (4.25 µg/mL). This indicates that the nanoparticles were more effective in capturing DPPH free radicals. Anticancer assays showed strong cytotoxic effects for all nanoparticles, with ZnO NPs exhibiting the highest activity (IC50: 1.94 μM for HEK 293 cells, 3.23 μM for HeLa cells), surpassing CuO and ZnO/CuO NPs. Cell viability for both HEK 293 and HeLa cells decreased as nanoparticle concentration increased, confirming dose-dependent cytotoxicity. The green synthesized metal oxides and their composite have the potential for biomedical applications.